Rice Bran and Probiotics Alter the Porcine Large Intestine and Serum Metabolomes for Protection against Human Rotavirus Diarrhea - Nealon, Nora Jean; Yuan, Lijuan; Yang, Xingdong; Ryan, Elizabeth P. (Frontiers in Microbiology, 2017)
Human rotavirus (HRV) is a leading cause of severe childhood diarrhea, and there is limited vaccine efficacy in the developing world. Neonatal gnotobiotic pigs consuming a prophylactic synbiotic combination of probiotics and rice bran (Pro+RB) did not exhibit HRV diarrhea after challenge. Multiple immune, gut barrier protective and anti-diarrheal mechanisms contributed to the prophylactic efficacy of Pro+RB when compared to probiotics (Pro) alone. In order to understand the molecular signature associated with diarrheal protection by Pro+RB, a global non-targeted metabolomics approach was applied to investigate the large intestinal contents (LIC) and serum of neonatal gnotobiotic pigs. The ultra-high performance liquid chromatography-tandem mass spectrometry platform revealed significantly-different metabolites (293 in LIC and 84 in serum) in the pigs fed Pro+RB compared to Pro, and many of these metabolites were lipids and amino acid/peptides. Lipid metabolites included 2-oleoylglycerol, (increased 293.40-fold in LIC of Pro+RB), which can modulate gastric emptying, and taurochenodeoxycholate, (increased 16.34-fold in LIC of Pro+RB), that can alter the intestinal lumen osmolarity and improve gut barrier function. Amino acid metabolites included cysteine, (decreased 0.40-fold in LIC and 0.62-fold in serum of Pro+RB), which has been found to reduce inflammation, lower oxidative stress and modulate mucosal immunity, and histamine (decreased 0.18-fold in LIC of Pro+RB and 1.57-fold in serum), which modulates local and systemic inflammatory responses as well as influences the enteric nervous system. Alterations to entire LIC and serum metabolic pathways further contributed to the anti-diarrheal and antiviral activities of Pro+RB such as sphingolipid, mono/diacylglycerol, fatty acid, secondary bile acid, and polyamine metabolism. Sphingolipid and long chain fatty acid profiles influenced the ability of HRV to both infect and replicate within cells, suggesting that Pro+RB created a protective lipid profile that interferes with HRV activity. Polyamines act on enterocyte calcium sensing receptors to modulate intracellular calcium levels, and may directly interfere with rotavirus replication. These results support that multiple host and probiotic metabolic networks, notably those involving lipid and amino acid/peptide metabolism, are important mechanisms through which Pro+RB protected against HRV diarrhea in neonatal gnotobiotic pigs.